Analisis penerapan nilai-nilai Al Islam dan Kemuhammadiyahan dalam perkuliahan - Tri Saswandi; Ayu Permata Sari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
This study aims to be Muhammadiyah assistance in evaluating to what extent the implementation of Al Islam Kemuhammadiyahan within the curriculum as a charity effort of Muhammadiyah Educational Institution, especially STKIP Muhammadiyah Sungai Penuh. This study is a field study because it was conducted in real and based on the factual data in the field. The type of this study is a descriptive-qualitative. Informants in this study are stakeholders, lecturers, and students of STKIP Muhammadiyah Sungai Penuh, who was registered in 2017/2018 academic year. Data collection was collected by using observation, interview, and documentation. Then, the data was analyzed through descriptive analysis by using the inductive method. By finding out to what extent the implementation of those values, the final goal of this study is as a starting point for the college, especially in reform their educational curriculum into the one which internalizes those values in all instructions of each study program.